PENERAPAN KARTU PERSEDIAAN SEBAGAI SARANA UNTUK MEMPERMUDAH PENCATATAN PERSEDIAAN PADA SALON RAMANDA AMPELDENTO KABUPATEN MALANG - Ellyn Eka Wahyu; Nilawati Fiernaningsih; Musthofa Hadi (Politeknik Negeri Malang, 2018)
This research was aimed to make an inventory card in terms to improve the process of stock-taking materials at Ramanda Beauty Shop Ampeldento, Malang. This research was an action research with 4 stages such as from Plan, Action, Observation, and also Reflection. The data was collected by interview method. To make sure that the owner of Ramanda Beauty Shop are able to use inventory card easily, researcher use a Technology Acceptance Model questionaire. The result of this research was the owner feel helped by the inventory card to record and inventarize the raw materials easily, because each time when there was a raw materials arrived, it must be recorded on the card, and if the employee wants to use the raw materials, the employee must update the card, so the movement of raw materials becomes more controlled and it can reduce excessive expends from the business owner's side.